Trends in intra-aortic balloon pump use in cardiogenic shock in the post-SHOCK II trial era. (14th October 2021) - Nan Tie, E; Dinh, D; Clark, D; Ajani, A E; Brennan, A; Cohen, N; Dagan, M; Shaw, J; Sebastian, M; Freeman, M; Oqueli, E; Reid, C; et al.
Abstract: Background: Myocardial infarction complicated by cardiogenic shock (MI-CS) has a poor prognosis, even with early revascularisation. Previously, intra-aortic balloon pump (IABP) use was thought to improve outcomes, but the SHOCK-II trial in 2012 found no survival benefit. Purpose: This study aimed to determine the trends in IABP use in patients with MI-CS undergoing percutaneous intervention (PCI) over time and characteristics associated with use. Methods: Between 2005–2018, patients presenting with MI-CS that underwent percutaneous coronary intervention (PCI) at a hospital participating in the Melbourne Interventional Group Registry were included. The primary outcome was the trend in IABP use over time. Secondary outcomes included mortality, 30-day MACCE (major adverse cardiovascular and cerebrovascular events) and predictors of outcome, determined via logistic regression. Results: Of the 1, 110 patients identified, IABP was used in 478 (43%). IABP was used more in patients with left main and left anterior descending culprit lesions (62% vs. 46%), lower ejection fraction (<35%; 18% vs. 11%), and pre-procedural inotrope use (81% vs. 73%), all p<0.05. IABP use was associated with higher inpatient bleeding (18% vs. 13%) and 30-day MACCE (58% vs. 51%), both p<0.05. The rate of MI-CS increased over time, but after 2012 there was a decline in IABP use (Figure 1). IABP use was a predictor of 30-day MACCE (OR 1.6, 95% CI 1.18–2.29, p=0.003). However, IABP was not associated with in-hospital, 30-day or long-term mortality (45% vs. 47%, p=0.44; 46% vs. 50%, p=0.25; 60% vs. 62%, p=0.39). Conclusions: Consistent with the SHOCK II trial, IABP use is not associated with reduced short- or long-term mortality, but in this study was associated with increased short-term adverse events. IABP use is declining, but is still used in sicker patients with greater myocardium at risk, given limited alternatives. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Melbourne interventional group